2018
DOI: 10.24929/fik.v8i2.647
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Rebusan Daun Salam Terhadap Penurunan Tekanan Darah Pada Lansia Dengan Hipertensi

Abstract: Daun salam (syzygiumpolyanthum) merupakan salah satu dari jenis terapi herbal yang digunakan untuk berbagai penyakit salah satunya yaitu untuk menangani penyakit hipertensi,untuk menurunkan hipertensi dibutuhkan 10 lembar daun salam dan 300 ml air lalu direbus hingga mendidih dan menyusut menjadi 200 ml dan dikonsumsi sebanyak 2 kali sehari pada pagi dan sore hari, masing-masing 100 ml. Penelitian ini bertujuan untuk mengetahui pengaruh air rebusan daun salam dalam menurunkan tekanan darah pada lansia di wilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Based on the characteristics of the respondents, it was found that the majority of respondents aged 45-59 years were 34 people (85.0%) in the Posbindu Buncis working area of the Kemirimuka health center, Depok city, Cityline with research conducted in Syaifurrahman Hidayat (2018) which showed that the age group in the treatment group was mostly at age 50-59 there were 13 people (43.30%), at age 70-79 there were 9 people (30.0%) and a small portion in the age range 60-69 were 8 people (26.70%). 8 Based on the research results of Arifal Aris (2018), show that the majority of the treatment group who suffered from hypertension were aged (51-60) years (53.15), because increasing blood pressure with age is very natural, this is due to natural changes in the heart, Blood vessels and hormone levels at old age are more susceptible to hypertension, because at that age the arteries are harder and less flexible to the blood, which can result in an increase in systolic blood pressure. This is also due to the many physiological declines in the body's systems with increasing age because in old age the blood vessels begin to lose their elasticity, which can affect the work of the cardiovascular system and can lead to hypertension, so in old age you are more susceptible to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the characteristics of the respondents, it was found that the majority of respondents aged 45-59 years were 34 people (85.0%) in the Posbindu Buncis working area of the Kemirimuka health center, Depok city, Cityline with research conducted in Syaifurrahman Hidayat (2018) which showed that the age group in the treatment group was mostly at age 50-59 there were 13 people (43.30%), at age 70-79 there were 9 people (30.0%) and a small portion in the age range 60-69 were 8 people (26.70%). 8 Based on the research results of Arifal Aris (2018), show that the majority of the treatment group who suffered from hypertension were aged (51-60) years (53.15), because increasing blood pressure with age is very natural, this is due to natural changes in the heart, Blood vessels and hormone levels at old age are more susceptible to hypertension, because at that age the arteries are harder and less flexible to the blood, which can result in an increase in systolic blood pressure. This is also due to the many physiological declines in the body's systems with increasing age because in old age the blood vessels begin to lose their elasticity, which can affect the work of the cardiovascular system and can lead to hypertension, so in old age you are more susceptible to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…These essential oils and tannins can increase urine production, and uric acid that is not needed by the body will be excreted in the urine through the kidneys (Setianingrum, 2019). 4 boiled bay leaves to each respondent every morning and evening for seven days, and found that boiled bay leaf water was effective in reducing uric acid levels in the elderly (Hidayat et al, 2013). Proven.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil ini didukung oleh Hidayat et al, (2018) Peneliti berasumsi bahwa adanya pengaruh air rebusan daun salam terhadap turunnya tekanan darah pada wanita lansia disebabkan karena konsumsi obat anti hipertensi yang disertai dengan konsumsi air rebusan daun salam sehingga lebih membantu untuk mengurangi tekanan darah tinggi dibandingkan dengan hanya mengkonsumsi obat antihipertensi. Pada penelitian ini responden yang berada pada kelompok intervensi lebih dominan dalam penurunan tekanan darah dibandingkan dengan kelompok kontrol.…”
Section: Tabel 4 Perbedaan Rata-rata Tekanan Darah Kelompok Intervens...unclassified